2020
DOI: 10.2196/13190
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Intelligent Serious Games for Children With Learning Difficulties: Observational Study

Abstract: Background Positive results can be obtained through game-based learning, but children with physical disabilities have fewer opportunities to participate in enjoyable physical activity. Because intelligent serious games can provide personalized learning opportunities, motivate the learner, teach 21st-century skills, and provide an environment for authentic and relevant assessment, they may be used to help children and adolescents with different kinds of learning disabilities to develop social and co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…Although the mean SUS score was quite similar for children with and without ADHD, we also considered that, in the context of this article, the performance time for each of the minigames and the maximum level reached by our users were both important (as shown in Figures 13-22). Children with ADHD (Minigame 1) Children with ADHD (Minigame 1) Children with ADHD (Minigame 1) Children with ADHD (Minigame 1) Children without ADHD (Minigame 3) Children without ADHD (Minigame 3) Children without ADHD (Minigame 3) Children with ADHD (Minigame 4) Considering the previous figures (Figures [13][14][15][16][17][18][19][20][21][22], we can observe that, in gen time required to finish each task was somewhat less in the case of children with but in some cases the children were very excited and somewhat nervous, know they were playing Alien Attack for the first time (a new game that none of thei knew yet) and they completed the tasks very quickly.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…Although the mean SUS score was quite similar for children with and without ADHD, we also considered that, in the context of this article, the performance time for each of the minigames and the maximum level reached by our users were both important (as shown in Figures 13-22). Children with ADHD (Minigame 1) Children with ADHD (Minigame 1) Children with ADHD (Minigame 1) Children with ADHD (Minigame 1) Children without ADHD (Minigame 3) Children without ADHD (Minigame 3) Children without ADHD (Minigame 3) Children with ADHD (Minigame 4) Considering the previous figures (Figures [13][14][15][16][17][18][19][20][21][22], we can observe that, in gen time required to finish each task was somewhat less in the case of children with but in some cases the children were very excited and somewhat nervous, know they were playing Alien Attack for the first time (a new game that none of thei knew yet) and they completed the tasks very quickly.…”
mentioning
confidence: 70%
“…This application could offer a potential non-pharmaceutical complement for the treatment of ADHD, since it is well known that games optimize motivation and treatment effects in these children. These types of technologies allow patients to remain at home during treatment, increasing their engagement, comfort, and satisfaction, which might potentiate the effect of the pharmacological therapy [16,17,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to students’ individual understandings of professionalism, personalised learning may be introduced to meet the differing needs of students. 38 Medical educators may consider using career choice motivation as an entry point to develop professionalism education programmes.…”
Section: Discussionmentioning
confidence: 99%
“…The study presented the details of the protocols and game design principles, but the games were not tested with the control group yet. Flogie et al [ 10 ] developed intelligent game interventions and used them with 51 children with learning difficulties in the mainstream Slovenian education system. The results showed that intelligent game interventions provide personalized education and can be helpful while designing the specialized curriculum.…”
Section: Introductionmentioning
confidence: 99%